Analyzing the Relationship between Performance Appraisal and Teacher Performance: Evidence from Cambodia - Chhy, Sothy; Kawai, Norimune (Angstrom Centre of Education, 2024)
In recent years, MoEYS has implemented a strategic plan to adhere to SDG 4 in promoting the quality of education. MoEYS also devotes itself to performance appraisals to measure and enhance teacher performance in Cambodian secondary schools. This quantitative study analyses the relationship between performance appraisal and teacher performance. It further examines the factors in current performance appraisal practices that influence teacher performance in public secondary in schools Phnom Penh, Cambodia. This study discovered the performance appraisal processes and methods that influence teacher performance. Our findings indicate a significant relationship between performance appraisal and teacher performance. Additionally, this study provides solutions to improve performance appraisal on target setting and performance rating assessment. It also provides a substantial roadmap for school principals to practice the performance appraisal more effectively to enhance teacher performance. Future research should consider performance appraisal practices that could influence teacher performance in Cambodian primary schools.